2017
DOI: 10.1089/lgbt.2016.0082
|View full text |Cite
|
Sign up to set email alerts
|

Understanding How Sexual and Gender Minority Stigmas Influence Depression Among Trans Women and Men Who Have Sex with Men in India

Abstract: Sexual and gender minority stigmas are associated with depression, with social support and resilient coping as mediators. In addition to stigma reduction interventions at the societal level, future interventions should focus on improving social support and promoting resilience among trans women and MSM in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 41 publications
4
50
0
1
Order By: Relevance
“…Appropriately powered studies specifically tailored for transgender women in sub-Saharan Africa would facilitate the robust analyses needed to fill gaps in knowledge of diverse transgender populations and to identify which transgender populations may be most vulnerable to HIV. Knowing that stigma drives both depression [ 61 ] and vulnerability to HIV infection, funders and national governments should invest in routine stigma surveillance [ 62 ] and the scale-up of effective transgender-inclusive stigma-reduction interventions [ 63 , 64 ] as key components of their HIV strategies. Transgender populations are emerging across sub-Saharan Africa: the data presented here suggest the need to understand the HIV epidemiology and specific HIV prevention and treatment needs of transgender populations in this region.…”
Section: Discussionmentioning
confidence: 99%
“…Appropriately powered studies specifically tailored for transgender women in sub-Saharan Africa would facilitate the robust analyses needed to fill gaps in knowledge of diverse transgender populations and to identify which transgender populations may be most vulnerable to HIV. Knowing that stigma drives both depression [ 61 ] and vulnerability to HIV infection, funders and national governments should invest in routine stigma surveillance [ 62 ] and the scale-up of effective transgender-inclusive stigma-reduction interventions [ 63 , 64 ] as key components of their HIV strategies. Transgender populations are emerging across sub-Saharan Africa: the data presented here suggest the need to understand the HIV epidemiology and specific HIV prevention and treatment needs of transgender populations in this region.…”
Section: Discussionmentioning
confidence: 99%
“…Many of transgender adults in India suffer from chronic conditions like diabetes, asthma, TB or HIV. Some studies have highlighted high substance use among the transgender community (Chakrapani et al, 2017;Goyal et al, 2014;Humsafar Trust, 2012;Muraleedharan et al, 2018). More than half the community consumed tobacco, which only made them more vulnerable to the disease since COVID-19 affects the respiratory system (CDC, 2020).…”
Section: Vulnerability Of Transgender To Covid-19 Infectionmentioning
confidence: 99%
“…High rates of negative mental health outcomes among TGD people are associated with a myriad of social and structural factors that work to impede or promote mental health. The most robust evidence lies in our understanding of how stigma, social exclusion and violence contribute negatively to mental health outcomes among trans people [ 61 , 63 , 70 , 71 , 72 ]. For example, Nuttbrock et al [ 73 ] reported a strong association between psychological and physical gender-related abuse and major depression among 571 trans women.…”
Section: Introductionmentioning
confidence: 99%